KEPUTUSAN STRATEGIS PELAKU UMKM DALAM MENGHADAPI KRISIS EKONOMI - Cahyadi, Luh Diah Citra Resmi; Pradnyani, Ni Luh Putu Sri Purnama (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This research aims to find out the strategic decision making made by MSME entrepreneurs in facing the crisis caused by the Covid-19 pandemic. The choice that can be taken by MSMEs is to do staretgi retrenchment and turn around strategies in order to survive in times of crisis. This research was conducted in Denpasar city and took 75 samples of MSMEs focused on the leading creative economy subsectors, namely fashion, craft and culinary. The results of this study found that the age indicators and educational background of MSMEs have a positive and significant effect while the internal locus of control indicators and the number of employees have a negative and significant effect on the decision of MSMEs using retrenchment. While all indicators do not have a significant effect on the decision of MSMEs using turn around strategies.